Pengembangan Web-based Nature Immersion sebagai Optimalisasi Digital Branding Ecotourism Telaga Madiredo - Yunika Dwi Pramudita; Robby Hilmi Rachmadian; Tasya Khairunisa; Ifadia Lailia Elissa; Alvito Rangga Pradipta; Sumarmi, Sumarmi (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Telaga Madiredo is a new tourist attraction in Malang Regency which combines the concepts of sustainable agriculture and ecotourism tourism. When viewed from the 4A elements of tourism, Telaga Madiredo has been classified as a tourist destination with superior attraction for all its potential. Madiredo Lake has a superior tourist attraction and continues to make improvements, the management of this tourism still faces problems, namely that it is not yet known to tourists on a massive scale. This problem refers to a decrease in the number of tourist visits, so that the income of local communities experiences depreciation. This service aims to improve the quality of digital branding, complete the tourism information system, and assist Madiredo managers to better understand social media management. In this regard, there needs to be a solution to overcome the problem by implementing Web-Based Nature Immersion based on Virtual Reality (VR) as an alternative means of digital promotion that is informative and representative to support Madiredo's more proportional digital branding. Seeing these facts, the Web-Based Nature Immersion media has a tendency to solve Madiredo's digital branding promotion problem by providing communicative tourism information technology in order to increase tourist visits and local community income.